Construction and optimization of ecological security patterns based on social equity perspective: A case study in Wuhan, China. (March 2022) - Cui, Xufeng; Deng, Wei; Yang, Jixin; Huang, Wei; de Vries, Walter T.
Highlights: Ecological security patterns was optimized considering social equity. 19 ecological sources and 51 corridors were identified by ESA-MCR Model. 1 amendment source and 25 amendment corridors were proposed by buffer analysis. Four types of ecological zones were proposed and joint management strategies were formulated. Abstract: Ecological Security Patterns (ESPs) are important nature-based solutions for ecological problems caused by urbanization and industrialization. Previous studies on ESPs focus on natural conditions only, yet do not incorporate the need for social equity. This study aims to address this quandary for the study area of Wuhan by identifying and extracting ecological sources and ecological corridors, followed by an ecological sensitivity assessment, minimum cumulative resistance model and buffer analysis, in order to construct and optimize ecological security patterns. The optimization for the construction of the most suitable ecological security patterns relies on social equity aspects, including the quality of urban ecological services and the improvement of the well-being of urban residents. The results demonstrate: (1) There are 19 ecological sources in Wuhan and 51 ecological corridors with a total length of 840.10 km. (2) To cater for the optimization of social equity needs, it was necessary to add one additional amendment source, with an area of 14.89 km 2, and 25 new amendment corridors with a total length of 287.8 km. (3) Optimizing the ecological security patterns in Wuhan is possible through the derivation of an ecological restoration area, ecological improvement area, ecological control area and ecological shield area. The results indicate the feasibility of simultaneously protecting urban ecological security and realizing social equity.